Hidden Harvest : The Global Contribution of Capture Fisheries - World Bank (Washington, DC, 2012)
This report provides a disaggregated profile of the world's small and large-scale fisheries and an estimate of its direct and indirect contributions to gross domestic product, food security, and rural livelihoods to uncover the hidden importance of the fisheries sector with a view to increasing its economic and environmental contributions in a sustainable manner. The study reveals serious information deficiencies that undermine decision makers' understanding of the importance of the fisheries sector. The study concludes that the contribution of the world's fisheries to national and global economies is greater than that generally recognized by decision makers and makes recommendations to reform, inform, and improve data collection regarding capture fisheries.